2019
DOI: 10.1080/00952990.2019.1628244
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of harmful use of alcohol in Nigeria: a systematic review and meta-analysis

Abstract: Background: Nigeria, the most populous country in Africa, has reported relatively high levels of alcohol misuse, yet limited resources to guide effective population-wide response. There is a need to integrate existing empirical information in order to increase the power and precision of estimating epidemiological evidence necessary for informing policies and developing prevention programs. Objectives: We aimed to estimate nationwide and zonal prevalence of harmful use of alcohol in Nigeria to inform public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Our findings agree with previous studies that found alcohol intake and/or binge drinking was associated with hypertension among Nigerians [50,62,63]. The high prevalence of alcohol use in this study population, which is similar to what obtains in the general population [64] suggests that alcohol use is another modifiable risk factor that can be targeted for both primary and secondary prevention of hypertension in Nigeria.…”
Section: Plos Onesupporting
confidence: 92%
“…Our findings agree with previous studies that found alcohol intake and/or binge drinking was associated with hypertension among Nigerians [50,62,63]. The high prevalence of alcohol use in this study population, which is similar to what obtains in the general population [64] suggests that alcohol use is another modifiable risk factor that can be targeted for both primary and secondary prevention of hypertension in Nigeria.…”
Section: Plos Onesupporting
confidence: 92%
“…A meta-regression model based on mean age from each study and adjusted for the study period was developed to determine prevalence distribution of hypercholesterolemia by the age of the Nigerian population over two separate years. As explained in previous studies 17,18 , we tested various models (linear, exponential, polynomial, logarithmic, etc.) to determine which was most predictive, representing the greatest proportion of variance(R 2 ) of the prevalence of hypercholesterolemia as explained by the inputted variables.…”
Section: Discussionmentioning
confidence: 99%
“…This study's finding of UGIB being more common in males is consistent with that from several authors (2, 5-7). The male preponderance may be explained by the higher prevalence of the underlying diseases and risk factors in Nigerian males, namely alcohol, smoking, peptic ulcers, and chronic liver disease (12)(13)(14)(15). Thirty-three percent of the patients with UGIB in our study were at least 60 years.…”
Section: Discussionmentioning
confidence: 67%